Analysis of scientific and technological indicators of environmental safety (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The main recommendations of this article mainly analizing the rate of harmful elements the period of explotation of the automobile impliments and its services to develop activity of automobile impliments of the explotation period.